Tornando-se um “acampado” a experiência das famílias organizadas pelo Movimento dos Trabalhadores Sem Teto (MTST) - Giaquinto, Marina Ferreira (2016)
Starting from Chicos Mendes's occupation analysis, this study intend to understand how is the struggle experience of The people of the Homeless Workers Movement (MTST) while they are camped. For this, however, we seek to recover the genesis of the problems that give, from one side, the formation of the movement for its integration to the socio-spatial inequalities from the city, and on the other hand, give basis for the social experiences lived and brought by people who enter in MTST while camping.This wide scenario will be the base to the preparation of the study and understanding of the encounter of these two distinct logics, among families who choose to be part of the movement and the political propositions of it. It will be in this interstice, understood by the movement only by the need of a housing, we will make this study through the pleople experience. Through the fieldwork done at the occupation and the literature reviews, it is evident in this study that MTST will be in a very distinguished suburb, similar to those which gave base to the appearance of urban movements from the 1970s and 1980s. And, therefore, will be by this widely modified scenario (both in the social experience of individuals and about the social management promoted by the state) that MTST seek to gain their legitimacy.